Pengaruh konsumsi biji rami (Linum usitatissium) terhadap menstruasi pada remaja putri di SMP Negeri 2 Langsa - Emilda Emilda; Idris M Daud (Jurnal SAGO Gizi dan Kesehatan, 2019)
Background: Flaxseed (Linum Usitatissimum) is a type of grain. Flaxseed is one of the best food sources of phytoestrogens with 379,380 mcg for every 100 grams. The contents of flaxseeds are omega 3, alpha linoleic fatty acids, lignans, vitamin B1, soluble fiber, protein, copper, manganese, magnesium, zinc, selenium and phosphorus. Flaxseed has a variety of benefits that are very good for health, one of which is launching menstruation.Objective: To find out the Effect of Consumption of Flax Seed (Linum Usitatissimum) on the Achievement of Adolescent Girls in SMP Negeri 2 Langsa in 2017Method: This research is a quasi experiment, using a Randomized Doublle Blinde Controlles Trial design. This research was conducted at 2 Langsa State Junior High School in 2017. This study consisted of 288 students of VII and VIII Public Middle Schools as many as 288 students. The analysis used to determine differences in menstrual cycles in the treatment and control groups used paired t-test.Results: The results of univariate and bivariate analysis studies where the results were obtained from 136 samples, there was no significant relationship between phytoestrogen consumption with menstrual time p = 0.375 and there was no relationship between phytoestrogen consumption with menstrual cycle and menstrual blood volume with p = 0.119 and p = 0.980. The duration of normal menstruation usually ranges from 5 to 7 days, some even up to 10 days. While the menstrual cycle will be different for each woman. Normally the cycle will repeat every 28 days, but there are also those who have a cycle of up to 42 days.Conclusion: Based on bivariate analysis shows the average menstrual cycle, the length of menstruation, menstrual volume, and Hb levels there were no significant differences in treatment between the pretest and posttest groups.